0444 Examining Sleep Duration and Social Jetlag From a Popular Wearable Sleep Tracker in France and Canada. (27th May 2020) - Elbaz, M; Robbins, R; Bouchequet, P; Czeisler, C; Leger, D
Abstract: Introduction: Many population estimates of sleep duration and quality rely primarily on self-reported data. Passive and ubiquitous digital tracking and wearable devices may provide more accurate estimates of sleep duration and quality. Our objective was to identify trends in sleep duration and social jetlag using data from a popular mobile sleep application (app) in France and Canada 'iSommeil.' Methods: We examined sleep using 8, 207 nights from iSommeil, a popular sleep-tracking app in France and Canada. In this analysis, we explored sleep data collected from this app from 2, 126 users. We examine sleep parameters by sex and between week and weekend. Specifically, we explore social jetlag, as calculated by the midpoint of sleep during the weekend, subtracted from the midpoint of sleep during the week. Results: Women represented 1, 254 (59.7%) of the sample and men represented 857 (40.3%) of the sample. Among women, 16.4% of the sample averaged <6 hours of sleep; 51.9% averaged 6-7.99 hours of sleep, and 31.7% averaged >=8 hours of sleep. Among men, 17.4% averaged <6 hours of sleep; 58.4% averaged 6-7.99 hours of sleep, and 24.2% averaged >=8 hours of sleep. Social jetlag scores among all users averaged 31.4, yet the average for men was 27.1 while that for women was 36.4. Conclusion: Our study of data from a popular sleep tracker in France and Canada showed that sleep duration of 6-7.99 hours was most observed among the majority of participants. Our results also showed that women had higher social jetlag scores than men. Future research may compare sleep measures obtained via wearable sleep trackers with validated research-grade measures of sleep. Support: